2018
DOI: 10.3389/fphys.2018.01771
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants in Preeclampsia: Lessons From Studies in Latin-American Populations

Abstract: Placental vascularization is a tightly regulated physiological process in which the maternal immune system plays a fundamental role. Vascularization of the maternal-placental interface involves a wide range of mechanisms primarily orchestrated by the fetal extravillous trophoblast and maternal immune cells. In a healthy pregnancy, an immune cross-talk between the mother and fetal cells results in the secretion of immunomodulatory mediators, apoptosis of specific cells, cellular differentiation/proliferation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 263 publications
1
33
0
Order By: Relevance
“…Pregnancy occurs against the genetic background and epigenetic programming of both the mother and the fetus. Maternal genetic variants affect the success of essential developmental processes such as decidualization and placentation, whereas both maternal and fetal genetics play a role in maintaining the delicate immune balance that characterizes embryonic and fetal development [68][69][70]. While genetic contributions to different complications in pregnancy are probably polygenic, genome-wide association studies (GWASs) have found genetic variants associated specifically with sPTB, illustrating how a mother's genetic makeup can set the stage for fetal development and pregnancy outcome even before conception [71][72][73].…”
Section: Genetics and Epigenetics For Characterizing Pregnancymentioning
confidence: 99%
“…Pregnancy occurs against the genetic background and epigenetic programming of both the mother and the fetus. Maternal genetic variants affect the success of essential developmental processes such as decidualization and placentation, whereas both maternal and fetal genetics play a role in maintaining the delicate immune balance that characterizes embryonic and fetal development [68][69][70]. While genetic contributions to different complications in pregnancy are probably polygenic, genome-wide association studies (GWASs) have found genetic variants associated specifically with sPTB, illustrating how a mother's genetic makeup can set the stage for fetal development and pregnancy outcome even before conception [71][72][73].…”
Section: Genetics and Epigenetics For Characterizing Pregnancymentioning
confidence: 99%
“…Pre‐eclampsia (PE) is a hypertensive disorder that affects 2%–8% of all pregnant women (Duley, ). PE is a polygenic disorder resulting from both foetal/placental and maternal genetic contributions and manifests as a complex phenotype (Michita, Kaminski, & Chies, ; Triche et al, ). In pathophysiological terms, PE is characterized by de novo hypertension after 20 weeks of gestation combined with proteinuria (Duley, ; Mol et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This allowed the determination of RNA levels but not protein levels. Another limitation is that RNA microarrays are unable to reveal the expression of polymorphic gene variants, which may have a role on preterm preeclampsia [115,116]. In future studies, next-generation sequencing may help reveal these variants.…”
Section: Discussionmentioning
confidence: 99%